The Effectiveness of Vaccination Against The Spread of COVID-19 with SEIR Mathematical Modeling in Gowa District - Syafruddin Side; Putri Kharina Mahathir Hulinggi; Husnul Khatimah Syam; Muhammad Irfan; Andi Gagah Palarungi Taufik (Jurnal Varian, 2021)
The spread of disease in epidemic range, endemic range, as well as in the pandemic range that is spreading of the disease can be stopped with getting vaccinated. The vaccines that are effective and efficient can be the missile that stopped this Covid-19 pandemic. The aim of this research is to (1) know the mapping model of mathematics SEIR in distributing vaccines toward the spread of Covid-19 in Kabupaten Gowa, (2) know the analysis and model simulation of mathematics SEIR in distributing vaccine toward the spread of Covid-19 in Kabupaten Gowa, also (3) know the impact of distributing vaccine toward the spread of Covid-19 in Kabupaten Gowa. The method we used is the literature review, the collecting data obtained by an interview and documentation review. The research result discovered that the model of mathematics SEIR is used to describe the distribution of vaccines toward the spread of Covid-19 in Kabupaten Gowa. The analysis and simulation results model of mathematics SEIR showed that the higher vaccines effectiveness and the number of the population in Kabupaten Gowa that already had vaccinated is higher, then showed no more spreads of Covid-19 and the pandemic is over.